Corruption and Fraudulent Activities in Higher Education: A Study of Literature - Harahap, Ludwina; Isgiyarta, Jaka (Jurnal Manajemen, 2023)
Corruption and other unethical behavior are essential and exciting issues, especially fraud or unethical behavior in universities or higher education. Despite of as a barometer of good behavior, the academician becomes a lousy example of corruption and unethical behavior or fraudulent activities. This study aims to review and learn more about corruption or other unethical behavior, especially in higher education institutions. This study examined articles from several journals using search engines, namely Scopus and Google Scholar, Emerald, Springer, and Proquest. About 20 main articles were used in this study to elaborate on terminology of corruption, corruption's causes and impact, particularly in higher education. The results show that some scholars give some terminology of corruption and indicate that corruption is linked to moral, cultural, political, and ideological perspectives, causing harm to governments and citizens. Results show that corruption relates to ideological, moral, cultural, and political perspectives, harming governments and citizens. It is an epidemic that distorts society, the rule of law, democracy, and markets, reduces the quality of life, and hinders the country's growth. It is time to eliminate and prevent corruption and other unethical behavior. This study might add to the literature on corruption in higher education by explaining the terminology of corruption, its cause, and its consequences. In-depth knowledge about corruption and others kind of fraud and unethical behaviors by the students earlier, it is hoped that the number of corruption in Indonesia will decrease.